P7.02 BEYOND BLOOD PRESSURE: IS ARTERIAL STIFFNESS MEASUREMENT THE FUTURE FOR PRIMARY CARE? A PILOT STUDY - A.H. Heald (Artery Research, 2009)
Background In primary care, much effort goes into risk factor management. Early recognition of vascular dysfunction in patients should inform intervention to reduce vascular risk. Very few studies have looked at the application of augmentation index (AI) measurement in primary care, particularly in those with impaired glucose handling (IGH) and type 2 diabetes, who have a higher than usual risk of cardiovascular disease. Arterial stiffness assessed via AI, with much less variation than BP, increases inexorably with age and is a potential marker for cardiovascular risk. AI is measured by applanation tonometry and is a non-invasive measure of arterial stiffness. Scientific aims The main aims are to describe the profile of augmentation index (AI) in patients at elevated cardiometabolic risk. Furthermore to assess its relation to central BP, body mass index (BMI) and HbA1C (type 2 diabetes only) in the age-matched normoglycaemic, IGH and type 2 diabetes participants. Plan of investigation for pilot study Using the established primary care register for individuals with IGH and type 2 diabetes in Central and Eastern Cheshire, age-matched consecutive attendees (between June and August 2009) at GP clinics in the area will undergo routine investigations. Central blood pressure and AI will be determined (Omron HEM-9000AI). Potential impact of pilot study To determine whether AI as a predictor of cardiovascular risk may be used to identify at risk individuals for more aggressive management. Evidence to support the use in Primary Care of AI and central BP measurement in patients with IGH and type 2 diabetes. To help GPs to understand the variation in AI by glucose tolerance status and to determine whether glycaemic control in type 2 diabetes is related to AI. In the next stage we will monitor prospectively the impact of targetted intensive management over time.